ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING PADA USAHA PENJAHIT DEWANTA - Mariana Tandi; Daniel Nemba Dambe (JURNAL ULET (Utility, Earning and Tax), 2022)
To determine the determination of the cost of production with the full costing method in dewanta tailor business. To determine the determination of the cost of production with the variable costing method in dewanta tailor business. Descriptive method is an analysis based on the description of the cost of production and the effect of the method of determining the cost of production so as to obtain an optimal profit. Data collection instruments used by researchers in the study are the recording of cost of goods manufactured and company documentation. Documentation is a method used to provide documents using accurate evidence from the recording of specific sources of information from essays or writings, books, etc., this documentation is used to obtain information and information about knowledge and proof of cost of production.